Lipid parameters of blood in veterans of war with post-traumatic stress disorder - M. N. Torgashov; A. I. Paltsev; V. S. Myakotnykh (Атеросклероз, 2013)
Investigated peculiarities of violations of lipid metabolism and symptoms of post-traumatic stress disorder (PTSD) in 161 patients – veterans of the military actions on the territory of Afghanistan and the Northern Caucasus in the age 25–69 years. The dependence of the formation of dyslipidemias and related changes of atherosclerosis in the young age of neuroendocrine effects, accompanying the effects of combat stress and promoting accelerated aging. After 15-25 years of participating in hostilities, the intensity of PTSD and its influence on the development of violations of lipid spectrum may decline, and the leading role in the pathogenesis of dyslipidemias goes to age-related changes that accompany a process of accelerated aging veterans of combat operations, and to pathological disorders of metabolism in the liver associated with alcohol abuse and the consequences suffered infectious diseases.